Sex differences in mapping and rhythm outcomes of a repeat atrial fibrillation ablation. Issue 23 (22nd January 2021) - Pak, Hui-Nam; Park, Je-Wook; Yang, Song-Yi; Kim, Min; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung
Abstract : Objective: The risk of procedure-related complications and rhythm outcomes differ between men and women after atrial fibrillation catheter ablation (AFCA). We evaluated whether consistent sex differences existed in mapping and rhythm outcomes in repeat ablation procedures. Methods: Among 3282 patients in the registry, we analysed 443 consecutive patients (24.6% female, 58.5±10.3 years old, 61.5% with paroxysmal atrial fibrillation) who underwent a second AFCA. We compared the clinical factors, mapping, left atrial (LA) pressure, complications and long-term clinical recurrences after propensity score matching. Results: LA volume index (43.1±18.6 vs 35.8±11.6 mL/m 2, p<0.001) was higher, but LA dimension (40.0±6.8 vs 41.6±6.3 mm, p=0.018), LA voltage (0.94±0.55 vs 1.20±0.68 mV, p=0.002) and pericardial fat volume (89.5±43.1 vs 122.1±53.9 cm 3, p<0.001) were lower in women with repeat ablation than in their male counterparts. Pulmonary vein (PV) reconnections were lower (58.7% vs 74.9%, p=0.001), but the proportion of extra-PV triggers (27.5% vs 17.0%, p=0.026) and elevated LA pulse pressures (79.7% vs 63.7%, p=0.019) was significantly higher in women than in men. There was no significant sex difference in the rate of procedure-related complications (4.6% vs 4.2%, p=0.791). During a 31-month (8–60) median follow-up, clinical recurrences were significantly higher in women after both the de novo procedure (log-rank p=0.039, antiarrhythmic drug (AAD)-free log-rank p<0.001) and the second procedure (log-rank p=0.006, AAD-free log-rank p=0.093). Female sex (HR 1.51, 95% CI 1.06 to 2.15, p=0.023), non-paroxysmal atrial fibrillation (HR 1.78, 95% CI 1.30 to 2.34, p<0.010) and extra-PV triggers (HR 1.88, 95% CI 1.28 to 2.75, p=0.001) were independently associated with clinical recurrences after repeat procedures. Conclusions: During repeat AFCA procedures, PV reconnections were lower in women than in men, and the existence of extra-PV triggers and an LA pressure elevation were more significant, which resulted in poor rhythm outcomes. Trial registration number: NCT02138695 .